PERBEDAAN PENGARUH SENAM AEROBIK MODERATE INTENSITY DAN HIGH INTENSITY TERHADAP KADAR GLUKOSA DARAH PADA PENDERITA DIABETES MELITUS TIPE II - Agustin, Defi Annisa; Tyas Sari Ratna Ningrum; Riska Risty Wardhani (Bajang Institute, 2025)
Type II diabetes mellitus occurs due to chronic metabolic disorders characterized by elevated glucose levels resulting from insulin resistance. Several factors contribute to increased glucose levels, including age, sex, body mass index (BMI), genetics, and occupation. If blood glucose remains uncontrolled and continues to rise, it can damage other organs and lead to complications. Moderate-intensity aerobic exercise consists of deliberately selected movements performed to music, targeting the aerobic system and carried out at a moderate intensity. In contrast, high-intensity aerobic exercise is a training program that combines moderate- and high-intensity movements to target both the aerobic and anaerobic systems. Both types of exercise aim to reduce blood glucose levels. Objective: This study aims to compare the effects of moderate- and high-intensity aerobic exercise on blood glucose levels in patients with type II diabetes mellitus. Method: This study employed quasi-experimental design with two-group pretest-posttest design. The sampling technique was purposive sampling, involving 16 participants who underwent an exercise program three times a week for four weeks. Group I performed moderate-intensity aerobic exercise, while Group II performed high-intensity aerobic exercise. A glucometer was used as the measurement tool. Results: Hypothesis tests I and II (p < 0.05) showed that both moderate- and high-intensity aerobic exercise had a significant effect on lowering blood glucose levels. Hypothesis test III (p < 0.05) indicated a significant difference between the effects of the two exercise intensities. Conclusion: There is a significant difference in the effects of moderate- and high-intensity aerobic exercise. High-intensity aerobic exercise has a greater effect on lowering blood glucose levels in patients with type II diabetes mellitus. Suggestion: Future researchers are encouraged to expand on this study by incorporating additional variables to provide more valuable scientific insights